The German language : a linguistic introduction - Boase-Beier, Jean (Blackwell Pub., 2003)
The German Language introduces students of German to a linguistic way of looking at the language. Written from a Chomksyan perspective, this volume covers the basic structural components of the German language: syntax, morphology, phonetics, phonology, and the lexicon.:.; Explores the linguistic structure of German from current theoretical perspectives.; Written from a Chomksyan perspective, this volume covers the basic structural components of the German language: syntax, morphology, phonetics, phonology, and the lexicon.; Serves as a valuable resource for students of German language and lite.